Pengembangan Komik Edukatif Sebagai Media Pembelajaran Siswa untuk Meningkatkan Kemampuan Pemecahan Masalah pada Materi Reproduksi Manusia - Balqis Putri Wardana Purba; Khairuna (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to develop an educational comic titled “Masa Pubertas: Menjelajahi Sistem Reproduksi” as a Biology learning medium on the topic of the human reproductive system to enhance students’ problem-solving skills. The research employed the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, questionnaires, as well as pretests and posttests, and were analyzed using descriptive qualitative and quantitative approaches. The results indicate that the educational comic is highly valid based on expert assessments, highly practical according to teachers and students, and effective in improving learning outcomes. In conclusion, the educational comic is feasible to be used as an innovative learning medium and has the potential to be further developed for other Biology topics. Keywords: ADDIE, Problem-Solving Skills, Learning Media, Educational Comic, Human Reproductive System